Extraction of carbohydrates (alginic acid) from the Grateloupia Doryphora species (brown algae - Ancon - Peru) - Acha de la Cruz, Otilia (1999)
From the leaves and mice of the species Grateoloupia Doryphora, crystalline mannitol and two oliguronic acids were extracted separately, both extractions were made in ethanol. Fucans were present in all sequential aqueous acidic and basic extractions. Each type of "fucan" contained varying proportions of fucose (higher percentage), galactose, mannose, xylose, glucuronic acid, sulfates, and small proportions of protein.The alginates were extracted directly in an alkaline medium, the difference in the sequential extractions in both parts of the plant was the greater amount of guluronic acid present in the alginic acid extracted in the roots of the plant.